Bifidobacteria shape antimicrobial T-helper cell responses during infancy and adulthood - Katrin Vogel; Aditya Arra; Holger Lingel; Dirk Bretschneider; Florian Prätsch; Denny Schanze; Martin Zenker; Silke Balk; Dunja Bruder; Robert Geffers; Thomas Hachenberg; Christoph Arens; et al. (Nature Communications, 2023)
Abstract Microbial infections early in life are challenging for the unexperienced immune system. The SARS-CoV-2 pandemic again has highlighted that neonatal, infant, child, and adult T-helper(Th)-cells respond differently to infections, and requires further understanding. This study investigates anti-bacterial T-cell responses against Staphylococcus aureus aureus, Staphylococcus epidermidis and Bifidobacterium longum infantis in early stages of life and adults and shows age and pathogen-dependent mechanisms. Beside activation-induced clustering, T-cells stimulated with Staphylococci become Th1-type cells; however, this differentiation is mitigated in Bifidobacterium-stimulated T-cells. Strikingly, prestimulation of T-cells with Bifidobacterium suppresses the activation of Staphylococcus-specific T-helper cells in a cell-cell dependent manner by inducing FoxP3+CD4+ T-cells, increasing IL-10 and galectin-1 secretion and showing a CTLA-4-dependent inhibitory capacity. Furthermore Bifidobacterium dampens Th responses of severely ill COVID-19 patients likely contributing to resolution of harmful overreactions of the immune system. Targeted, age-specific interventions may enhance infection defence, and specific immune features may have potential cross-age utilization.